Faktor Yang Mempengaruhi Minat Mahasiswa Dalam Mata Kuliah Management Accounting - Merna Surjadi; Tandry Whittleliang Hakki; Silviana Sagita (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Every prospective student in determining their choice to continue their education in college and choosing a study program is certainly influenced by many factors, both factors from within the individual and factors from outside the individual. In general, every prospective student determines their choice of a study program based on their preferences, interests, talents, or abilities in that field. Because what they choose will determine the next steps in their lives. This study aims to analyze the influence of Emotional Intelligence and Intellectual Intelligence and Student Understanding on Student Interest in Management Accounting Courses. This study uses a quantitative correlational method where sampling is done using the Slovin formula and using purposive sampling techniques and data collection methods through distributing questionnaires. The study uses SPSS 25.00 and hypothesis testing uses Multiple Regression Analysis. This study uses primary data conducted by distributing questionnaires to students in the cities of Jakarta and Bandung. The results of the study indicate that Emotional Anxiety has a significant effect on student interest in management accounting courses, intellectual intelligence has a significant effect on student interest in management accounting courses and student experience does not have a significant effect on student interest in management accounting courses.